Ochrona praw dziecka w świetle regulacji prawa międzynarodowego i polskiego - Szmigel, Kinga (Wydawnictwo Naukowe UAM, 2018)
Celem artykułu jest przedstawienie zagadnienia ochrony praw dziecka w świetle regulacji prawa polskiego i międzynarodowego. Rozważania dotyczące podstaw prawnych ochrony praw dziecka podzielono na cztery podpunkty. W pierwszej kolejności zostało omówione prawo do wychowania w rodzinie, która jest podstawową jednostką społeczną. Kolejny podpunkt traktował o prawie do godziwych warunków socjalnych. Następne rozważania dotyczyły prawa do nauki jako prawa kulturalnego przysługującemu każdemu dziecku. Poruszono także zagadnienie prawa do życia, które jest niezbywalne i nieodzownie połączone z prawem do ochrony zdrowia.

The purpose of this article is to present the protection of children's rights in the light of Polish and international legal regulations. Considerations regarding the legal basis for the protection of children's rights were divided into four parts. The right to be brought up in the family as a basic unit of society was discussed first of all. The next part elaborates on the right to decent social conditions. And the following deliberations are related to the right to education as the right to culture to which each and every child is entitled. The right to live as the inalienable right which is inevitably combined with the right to health protection was described as well.
Protection of children’s rights in Polish and international law
Keywords: ochrona praw dziecka; protection of children's rights; Rzecznik Praw Dziecka; Children’s Ombudsman; przestrzeganie praw dziecka; observance of children's rights